A smart handover strategy for 5G mmWave dual connectivity networks - Abdullah, Nor Fadzilah; Gannapathy, Vigneswara Rao; Nordin, Rosdiadee; Abu-Samah, Asma (Institute of Electrical and Electronics Engineers Inc., 2023)
The consideration of millimeter wave (mmWave) bands and ultra-dense deployment have emerged as essential enabling solutions in Fifth Generation (5G) networks. However, these solutions result in a significant surge in the number of handovers (HOs), leading to an increased occurrence of unnecessary handovers and a higher likelihood of dropped connectivity. Hence, designing a robust mobility technique that facilitates seamless connections to the user equipment (UE) has become crucial and challenging. One of the essential HO optimisation techniques is referred to as Mobility Robustness Optimisation (MRO), which focuses on adapting HO Control Parameters (HCPs) such as Hysteresis Margin (HM) and Time-to-Trigger (TTT). While it was originally designed for 4G and subsequently enhanced for 5G, the effectiveness of this functionality requires further refinement to meet the demands of future mobile networks. Existing MROs approaches primarily focus on UE mobility and heavily rely on metrics such as Received Signal Reference Power (RSRP) and Received Signal Reference Quality (RSRQ). However, these approaches tend to overlook critical handover challenges, including the widespread deployment of small cells, which is crucial in 5G mmWave networks, as well as issues related to interference and channel intermittency. This research proposes a Smart Handover Strategy (SHS) mechanism to autonomously fine-tune handover control parameters, including HM and TTT, by utilising real-time channel conditions assessed through the Signal-to-Interference-Noise Ratio (SINR), thereby ensuring precise parameter adjustments. The utilisation of SINR in this proposed mechanism aims to address handover challenges arising from interference, high intermittent, and unpredictable behaviours encountered in 5G mmWave wireless channels. The primary goal of this mechanism is to facilitate seamless handovers as UE transitions from one Base Station (BS) to another in a dual connectivity multi-radio network. The developed algorithm underwent testing using a 5G mmWave statistical channel model that emulates a dynamic channel matrix, including fading and the Doppler effect. The Network Simulator 3 (NS3) software was utilised to analyse and evaluate the performance of the SHS mechanism, specifically in terms of latency and throughput. The simulation results demonstrate the remarkable effectiveness of the SHS mechanism, showcasing a substantial improvement. In comparison to other handover enhancement techniques, the SHS mechanism achieves a notable increase of over 7% (38 Mbps) in PDCP throughput and a significant reduction of more than 56% (1.87 ms) in latency. Notably, when compared to fixed or traditional handover techniques in digital beamforming configurations, the SHS mechanism exhibits an impressive enhancement, with over 15% (80 Mbps) increase in PDCP throughput and a substantial reduction of more than 77% (4.85 ms) in latency.